Caregivers’ perception and acceptance of malaria vaccine for Children - Bam Victoria; Mohammed Abdulai; Kusi Amponsah Abigail; Armah Jerry; Lomotey Alberta Yemotsoo; Budu Hayford Isaac; Poku Collins Atta; Kyei-Dompim Joana; Dwumfour Catherine (Public Library of Science, 2025)
Background
Malaria is a disease of public health concern and in endemic areas, pregnant women and children under-five years are vulnerable to the disease. The introduction of the pilot program of a malaria vaccine for children under-five years in Ghana is an intervention to further reduce the burden of the disease. However, the availability of the vaccine does not necessarily mean it will be accepted by the public. This is why the perceptions and acceptance of the vaccine among mothers of these children are worth exploring.
Method
A descriptive qualitative study, with the aid of a semi-structured interview guide, was utilized in collecting data from ten (10) purposively sampled mothers whose children were taking the malaria vaccine in a municipality in Ghana. Written informed consent was obtained from all participants. The audiotaped interviews were transcribed verbatim and inductively analyzed into themes describing their perceptions and acceptance.
Results
Participants were aged between 22 and 40 years with eight (8) of them married. Three themes emerged from the study. "Awareness of malaria and the malaria vaccine" (1), “Insight into the malaria vaccine” (2), where participants communicated the beliefs and judgments formed on the vaccine, its benefits, and the need for vaccinating their children. With the third theme "Reaction to vaccine” (3), participants communicated their motivation to vaccinate their children and their concerns about the administration of the vaccine.
Conclusion
The caregivers had positive perceptions about the malaria vaccine for children, with fewer hospital admissions and saving money as some benefits. Healthworkers played a significant role in influencing the acceptance of the vaccine. However, the fear of the unknown concerning the side effects of the vaccine serve as a possible barrier to recommending the vaccine to other caregivers. Health education must also address the fears of caregivers in order to enhance recommending the malaria vaccine to other caregivers and promote uptake of the vaccination.